Standardisation of von Willebrand Factor in Therapeutic Concentrates: Calibration of the 1st International Standard for von Willebrand Factor Concentrate (00/514) - Hubbard, Anthony R.; Sands, Dawn; Chang, Andrew C.; Mazurier, Claudine (Thrombosis and Haemostasis, 2002)
An international study involving 26 laboratories assayed two candidate von Willebrand Factor (VWF) concentrates (B and C) for VWF:Antigen (VWF:Ag), VWF:Ristocetin Cofactor (VWF:RCo) and VWF:Collagen binding (VWF:CB) relative to the 4th International Standard Factor VIII/VWF Plasma (4th IS Plasma) (97/586). Estimates of VWF:Ag showed good agreement between different methods, for both candidates, and the overall combined means were 11.01 IU/ml with inter-laboratory variability (GCV) of 10.9% for candidate B and 14.01 IU/ml (GCV 11.8%) for candidate C. Estimates of VWF:RCo showed no significant difference between methods for both candidates and gave overall means of 9.38 IU/ml (GCV 23.7%) for candidate B and 10.19 IU/ml (GCV 24.4%) for candidate C. Prior to the calibration of the candidates for VWF:CB it was necessary to calibrate the 4th IS Plasma relative to local frozen normal plasma pools; there was good agreement between different collagen reagents and an overall mean of 0.83 IU per ampoule (GCV 11.8%) was assigned. In contrast, estimates of VWF:CB in both candidates showed large differences between collagen reagents with inter-laboratory GCV’s of 40%. Candidate B (00/514) was established as the 1st International Standard von Willebrand Factor Concentrate by the WHO Expert Committee on Biological Standardisation in November 2001 with assigned values for VWF:Ag (11.0 IU/ampoule) and VWF:RCo (9.4 IU/ampoule). Large inter-laboratory variability of estimates precluded the assignment of a value for VWF:CB.
Keywords: von Willebrand Factor; von Willebrand Disease; International Standard; Factor VIII concentrates